Management for grain sorghum cultivation under saline water irrigation - Miguel J. M. Guimarães; Welson L. Simões; Alessandra M. Salviano; Anderson R. de Oliveira; Jucicléia S. da Silva; Juliane R. A. Barros; Lilia Willadino (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In order to obtain an efficient cultivation of grain sorghum in production systems that use saline water, an adequate management becomes necessary for maximizing its production. The present study aimed to evaluate the effect of the application of leaching fractions in the saline water irrigation management on the production of sorghum varieties and on the distribution of water and salts in the soil profile, under semiarid conditions. The study was carried out in the municipality of Petrolina, semiarid region of Brazil. The experimental design was randomized blocks, with four replicates, in split-split plots; four leaching fractions (LF): 0, 5, 10, and 15% with saline water from artesian well in the plots, three varieties of grain sorghum: 1011-IPA, 2502-IPA and Ponta Negra in the subplots, and two crop cycles (1st and 2nd cut) in the sub-subplots. The evaluated variables were distribution of water and salts in the soil profile, biometric variables, fresh biomass, dry biomass, and grain yield. Application of leaching fractions of up 15% in saline water irrigation promotes better distribution of salts in the soil profile, with increments of up to 60% in the grain yield of the sorghum varieties evaluated. The production of the varieties 1011-IPA and Ponta Negra is a feasible alternative in systems irrigated with saline water with average electrical conductivity of 4.19 dS m-1, in Ultisol, under semiarid conditions.